CLINICAL MANIFESTATIONS OF CHILDREN AND ADOLESCENTS WITH COVID-19: REPORT OF THE FIRST 115 CASES FROM SABARÁ HOSPITAL INFANTIL - Anna Clara Rabha; Francisco Ivanildo de Oliveira Junior; Thales Araújo de Oliveira; Regina Grigolli Cesar; Giuliana Fongaro; Roberta Ferreira Mariano; Clarice Neves Camargo; Fátima Rodrigues Fernandes; Gustavo Falbo Wandalsen (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To describe the clinical manifestations and severity of children and adolescents affected by COVID-19 treated at Sabará Hospital Infantil. Methods: This is a cross-sectional, retrospective, and observational study. All cases of COVID-19 confirmed by RT-qPCR of patients seen at the hospital (emergency room, first-aid room, and ICU) were analyzed. The severity of the cases was classified according to the Chinese Consensus. Results: Among the 115 children included, a predominance of boys (57%) was verified, and the median age was two years. A total of 22 children were hospitalized, 12 in the ICU. Of the total, 26% had comorbidities with a predominance of asthma (13%). Fever, cough, and nasal discharge were the most frequent symptoms. Respiratory symptoms were reported by 58% of children and gastrointestinal symptoms, by 34%. Three children were asymptomatic, 81 (70%) had upper airway symptoms, 15 (13%) had mild pneumonia, and 16 (14%) had severe pneumonia. Hospitalized children were younger than non-hospitalized children (7 months vs. 36 months). In hospitalized patients, a higher frequency of irritability, dyspnea, drowsiness, respiratory distress, low oxygen saturation, and hepatomegaly was observed. Chest radiography was performed in 69 children with 45% of abnormal exams. No child required mechanical ventilation and there were no deaths. Conclusions: Most of children and adolescents affected by COVID-19 had mild upper airway symptoms. Clinical manifestations of COVID-19 were more severe among younger children who exhibited gastrointestinal and respiratory symptoms more frequently.